PENGEMBANGAN SISTEM TRANSPORTASI MULTI MODA DALAM KERANGKA EFISIENSI LOGISTIK MASYARAKAT PULAU DI KABUPATEN PANGKEP PROVINSI SULAWESI SELATAN - AS, Nur Syam (Teknosains: Media Informasi Sains dan Teknologi, 2016)
Based on the research results, it appears that the development of multimodal transportation system in Pangkep within the framework of logistik efficiency island communities to do with optimizing the utilization of large rivers that cross the territory Pangkep. The third river is the national road network services, in addition is located adjacent to the vertices of the other transport, such as road transport terminals, ports and railway station plan. The river dock location that is on one site with markets and shops will facilitate the transport of goods and facilitate the public to transact their catch in the territorial waters of the island. The development of multimodal transportation system in Pangkep is needed, in addition to the potential that surrounded him, also have barriers and problems faced by the island community. The high price of goods on the island due to the lack mode of transport that can be used by local communities in accordance with the movement of goods and capacity needs. Volume logistik needs of the island community based food standards, thus requiring facilities more adequate transport services through the provision of specialized vessels, ie vessels with a capacity of 350 DWT. This ship is a type of vessel that can be saved by the government as a ship pilot for remote areas and islands (promote the trade ships and ships follow the trade). The transport system development course provides broad direction of regional development that can improve the welfare of the people in the island territories Pangkep.